Factor VIII, Protein C and Cardiovascular Disease Risk: The REasons for Geographic and Racial Differences in Stroke Study (REGARDS) - Zakai, Neil A.; Judd, Suzanne E.; Kissela, Brett; Howard, George; Safford, Monika M.; Cushman, Mary (Thrombosis and Haemostasis, 2018)
Background Haemostatic balance represented by low protein C (PC) and elevated factor VIII (FVIII) has been inconsistently associated with stroke and coronary heart disease (CHD) risk.Objective This article assesses whether an elevated FVIII and a low PC would increase cardiovascular risk more than either individually.Patients and Methods REGARDS recruited 30,239 black and white U.S. participants aged ≥ 45 years between 2003 and 2007. FVIII and PC were measured in a case–cohort sample of 646 stroke, 654 CHD, and a 1,104-person random sample with follow-up for approximately 4.5 years. Hazard ratios (HRs) were estimated using Cox models adjusted for demographic and cardiovascular risk factors.Results Elevated FVIII (per standard deviation [SD] increase) was associated with increased risk of both stroke (HR, 1.26; 95% confidence interval [CI], 1.08, 1.46) and CHD (HR, 1.52; 95% CI, 1.29, 1.79), while there was no association of PC per SD decrease. For PC, there was a trend towards increased cardiovascular disease risk in the lowest values (bottom 5%). For stroke, there was no interaction between FVIII and low PC (pinteraction = 0.55). For CHD, the adjusted HR of FVIII per SD increase was significantly greater with PC in the bottom 5% (HR, 3.59; 95% CI, 1.39, 8.29) than PC in the upper 95% (HR, 1.45; 95% CI, 1.23, 1.71; pinteraction = 0.07).Conclusion Higher FVIII was associated with both CHD and stroke risk and the risk potentiated by low PC for CHD. Findings demonstrate that risks for cardiovascular diseases conferred by adverse levels of haemostasis biomarkers may be augmented by levels of other biomarkers.
Keywords: coronary disease; epidemiology; factor VIII; protein C; stroke